A prospective observational cohort study to evaluate patients' experience during sequential cataract surgery under monitored anesthesia care and topical anesthesia. Issue 47 (20th November 2020) - Heard, Jarrett A.; Zacarias, Alicia A. Gonzalez; Lawrence, Alec T.; Stoicea, Nicoleta; Palettas, Marilly; Fiorda-Diaz, Juan; Guertin, Michael G.; Tandon, Amit; Lowery, Deborah S.
Abstract : Abstract: Cataract surgery is the most common ambulatory surgery at our outpatient surgery center. Several studies have shown that patients with bilateral cataracts may experience different levels of anxiety, pain, and awareness during the first and second cataract extraction. A prospective observational cohort study was conducted at The Ohio State University Wexner Medical Center Eye and Ear Institute in order to compare anxiety, general comfort, awareness, and pain levels in patients undergoing sequential cataract surgeries. Likert and numerical rating scale were used to assess the outcomes. Patients receiving monitored anesthesia care and topical anesthesia were included. A total of 198 patients were enrolled in this study, 116 patients (59%) were female and 157 patients (78%) were Caucasians with a median age of 67 years among participants. Patients with rating "no anxiety" or feeling "somewhat anxious" were significantly higher during surgery 2 ( P =< .001). Most of the patients felt "extremely comfortable" during surgery 1 when compared to surgery 2 (54% vs 42.9%; P = .08). No significant differences were found between surgeries regarding intraoperative awareness ( P = .16). Overall, patients experienced mild pain during both procedures (92.4% in surgery 1 compared to 90.4% in surgery 2; P = .55). During the postoperative visit, 54% of the patients associated surgery 2 with less anxiety levels, 53% with no differences in general comfort, 60% felt more aware, and 59% had no differences in pain levels. Previous exposure to surgery could have been associated with a significant reduction in anxiety levels reported during surgery 2. Non-pharmacological strategies aiming to reduce perioperative anxiety may be considered an alternative or additional approach to premedication in patients undergoing consecutive cataract surgeries. Abstract : Supplemental Digital Content is available in the text